Three rare Rdzogs chen texts of the Bdud-ʼjoms tradition - Bdud-ʼjoms-gliṅ-pa, Gter-ston, b. 1835; Bde-baʼi-rdo-rje; Padma-bkra-śis (Kunsang Topgay, 1976)
Meditational texts of the Nyingmapa tradition of Tibetan Buddhism.